Electrical properties of Nd-doped BiFeO3 ceramics - Siriprapa P. (Taylor and Francis Ltd., 2015)
The effects of Nd2O3 dopant on structure and dielectric properties of Bi1-xNdxFeO3 ceramics, when x = 0, 0.05, 0.10, 0.15 and 0.20 mol fraction, were studied. The powders were pressed and sintered at temperatures in between 825-900?C for 2 h to form ceramics. The optimum sintering temperature was found to be 850?C where maximum density was achieved. Chemical composition examined using XRD indicated an existence of polycrystalline BNFO with rhombohedral structure. An increase in Nd2O3 content improved densification and reduced grain size of the ceramics. Electrical conductivity values were found to decrease with increasing Nd-doping content, which could be correlated to the improvement of dielectric and ferroelectric properties. Copyright © 2013 Taylor & Francis Group, LLC.